2006
DOI: 10.1190/1.2202671
|View full text |Cite
|
Sign up to set email alerts
|

A seafloor observatory to monitor gas hydrates in the Gulf of Mexico

Abstract: Background Gas hydrates are solid structures composed of gas molecules encased in cages of water molecules. Most interesting to the energy community are hydrates that contain hydrocarbon gases. In the northern Gulf of Mexico, hydrates of this type form in water depths greater than 450m and often occur in mounds located where faults intersect the sea floor. Typically, these hydrates consist of sea water from which the salt has been excluded and gases that have migrated up faults from buried hydrocarbon reservoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…1) gas hydrate site is located on the eastern side of Mississippi Canyon along the continental slope of the northern GOM. It is home to a seafloor observatory where gas hydrate dynamics are monitored (McGee, 2006;Lapham et al, 2008;Macelloni et al, 2013). The site was discovered during dives of the Johnson Sea Link (JSL) research submersible in 2002 (dives 4414 and 4415).…”
Section: Site Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) gas hydrate site is located on the eastern side of Mississippi Canyon along the continental slope of the northern GOM. It is home to a seafloor observatory where gas hydrate dynamics are monitored (McGee, 2006;Lapham et al, 2008;Macelloni et al, 2013). The site was discovered during dives of the Johnson Sea Link (JSL) research submersible in 2002 (dives 4414 and 4415).…”
Section: Site Characteristicsmentioning
confidence: 99%
“…McGee, 2006;Lapham et al, 2008;Ingram et al, 2010). The physical and biogeochemical processes associated with gas hydrates and cold seep systems are increasingly understood (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Woolsey Mound, MC118, is the site of the Gulf of Mexico Hydrates Research Consortium's (GOMHRC) Seafloor Observatory [McGee, 2006], where the HSZ has been the subject of intense and continuing investigation since 2005 [Lutken et al, 2011a]. The onekilometer-diameter carbonate/hydrate mound, located on the continental slope, in~890 m water depth ( Fig.…”
Section: Previous Work At Woolsey Moundmentioning
confidence: 99%
“…Pizzi et al, (2012) and Simonetti et al, (2013) have conducted very accurate analyses of fault movements detectable on high resolution chirp data. They have both found that all master faults have been active in very recent geologic time.…”
Section: Dynamics Of the Hydrate Stability Zonementioning
confidence: 99%
“…The main goal of the Consortium is to install and operate the first permanent sea-floor monitoring station which will monitor more or less continuously the Gas Hydrates Stability Zone (GHSZ) via geochemistry, geophysical and biological measurements (McGee, 2006). In order to facilitate the best observatory site selection, over the last few years the GOMHRC has been carrying out several seismo-acoustic surveys around the Northern Gulf of Mexico continental Shelf using the Surface Source Deep Receiver (SSDR) technique (McGee, 2000).…”
Section: Introductionmentioning
confidence: 99%